2002
DOI: 10.1103/physrevlett.89.148305
|View full text |Cite
|
Sign up to set email alerts
|

Instability of a Lamellar Phase under Shear Flow: Formation of Multilamellar Vesicles

Abstract: The formation of closed-compact multilamellar vesicles (referred to in the literature as the "onion texture") obtained upon shearing lamellar phases is studied using small-angle light scattering and cross-polarized microscopy. By varying the shear rate gamma;, the gap cell D, and the smectic distance d, we show that: (i) the formation of this structure occurs homogeneously in the cell at a well-defined wave vector q(i), via a strain-controlled process, and (ii) the value of q(i) varies as (dgamma;/D)(1/3). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
51
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 18 publications
9
51
1
Order By: Relevance
“…If inverse proportionality between the characteristic time and applied shear rate t ~ γ -1 is observed in this plot, the onion formation can be scaled by the applied strain. Several scientists confirmed that the scaling behavior with the strain successfully holds [8,31,33,34]. However, our results show no inverse proportionality against the shear rate.…”
Section: T 1 and T 2 In The Particle-containing Systemscontrasting
confidence: 54%
See 3 more Smart Citations
“…If inverse proportionality between the characteristic time and applied shear rate t ~ γ -1 is observed in this plot, the onion formation can be scaled by the applied strain. Several scientists confirmed that the scaling behavior with the strain successfully holds [8,31,33,34]. However, our results show no inverse proportionality against the shear rate.…”
Section: T 1 and T 2 In The Particle-containing Systemscontrasting
confidence: 54%
“…In fig. 2, transient viscosity at different γ are summarized as a function of the applied shear strain γ = γ t. Transient viscosity increases with double steps as already reported [9,19,31,33]. The double step behavior gradually softens and disappears as γ is increased.…”
Section: Shear-induced Onion Phase Formation In the Free-particle Systemmentioning
confidence: 69%
See 2 more Smart Citations
“…Diat and Roux first discovered 20 years ago closely-packed multilamellar vesicle (MLV) structures, so-called the onion phase, in nonionic surfactant-water mixtures under shear flow. [2][3][4] In the last two decades, this onion structure has been studied experimentally using light, 2,4-8 neutron, 2,4,9 and X-ray scattering, 7,8,10 and also by freeze-fracture electron microscopy, 5 and the rheo-NMR method. [11][12][13] Its rheology has been of large interest.…”
Section: Introductionmentioning
confidence: 99%